The Poltergeist by William G. Roll - Laursen, Christopher (Journal of Scientific Exploration, 2013)
What makes a book written about poltergeists in the early 1970s relevant today? There have been numerous books published since dedicated to analysis of this spontaneous, physical phenomena. Notable are those by Alan Gauld and Tony Cornell (1979), D. Scott Rogo (1979, 1986), Colin Wilson (1981), John and Anne Spencer (1997), and most recently Claude Lecouteux (in French 2007, English translation 2012), P. G. Maxwell-Stuart (2012), and Geoff Holder (2012, 2013). Preceded by key book-length examinations by Sacheverell Sitwell, Harry Price, Herbert Thurston, Hereward Carrington, Nandor Fodor, and A. R. G. Owen, what distinguishes William Roll’s The Poltergeist from all of these works is that it is based on a sustained, systematic series of ongoing poltergeist investigations conducted by Roll himself that further developed his hypothesis that this phenomenon emanated from living people. Alongside longstanding propositions that the poltergeist is a spirit of the dead or a product of human deception, Roll’s recurrent spontaneous psychokinesis (RSPK) remains among the most discussed ideas about this strange phenomenon. Through six detailed investigative summaries and a brief historical review, Roll clearly outlined the problems of the poltergeist and the methodologies that through over a dozen years of investigation he felt could advance the study. Today, The Poltergeist vitally continues to refresh analytical viewpoints, essential reading for anyone venturing into field investigations of continuing anomalous phenomena.